Case Report: A Case Study Significance of the Reflective Parenting for the Child Development - Kostova, Zlatomira (Frontiers in Psychology, 2021)
There are studies that connect the “child” in the past with the “parent” in the present through the prism of high levels of stress, guilt, anxiety. This raises the question of the experiences and internal work patterns formed in childhood and developed through parenthood at a later stage. The article (case study) presents the quality of parental capacity of a family raising a child with an autism spectrum. The abilities of parents (the emphasis is on the mother) to recognize and differentiate the mental states of their non-verbal child are discussed. An analysis of the parental representations for the child and the parent–child relationship is developed. The parameters of reflective parenting are measured. The methodology provides good opportunities for identifying deficits in two aspects: parenting and the functioning of the child itself. Without their establishment, therapy could not have a clear perspective. An integrative approach for psychological support of the child and his family is presented: psychological work with the child on the main areas of functioning, in parallel with the therapy conducted with the parents and the mother, as the main caregiver. The changes for the described period are indicated, which are related to the improvement of the parental capacity in the mother and the progress in the therapy in the child. A prognosis for ongoing therapy is given, as well as topics that have arisen in the process of diagnostic procedures.